Facile and scalable synthesis of sub-micrometer electrolyte particles for solid acid fuel cells. Issue 39 (13th June 2018) - Lohmann-Richters, F. P.; Odenwald, C.; Kickelbick, G.; Abel, B.; Varga, Á.
Abstract : Stable sub-micrometer CsH2 PO4 electrolyte particles for application in solid acid fuel cells are precipitated in a facile, scalable way. Abstract : Nanostructuring fuel cell electrodes is a viable pathway to reach high performance with low catalyst loadings. Thus, in solid acid fuel cells, small CsH2 PO4 electrolyte particles are needed for the composite powder electrodes as well as for thin electrolyte membranes. Previous efforts have resulted in significant improvements in performance when using sub-micrometer CsH2 PO4 particles, but laborious methods with low throughput were employed for their synthesis. In this work, we present a simple, robust, and scalable method to synthesize CsH2 PO4 particles with diameters down to below 200 nm. The method involves precipitating CsH2 PO4 by mixing precursor solutions in alcohol in the presence of a dispersing additive. The influence of the concentrations, the batch size, the solvent, and the mixing process is investigated. The particle size decreases down to 119 nm with increasing amount of dispersing additive. Mixing in a microreactor leads to a narrower particle size distribution. The particle shape can be tuned by varying the solvent. The ionic conductivity under solid acid fuel cell conditions is 2.0 × 10 −2 S cm −1 and thus close to that of CsH2 PO4 without dispersing additive.